RUU TNI dalam Sorotan Media: Representasi Kekuasaan Analisis Wacana Kritis Teori Van Dijk - Nur Azzahra, Aulivia Harindi; Riza, Raisha Nurul (Literasi : Jurnal Bahasa dan Sastra Indonesia serta Pembelajarannya, 2025)
This study aims to examine the representation of power in media coverage related to the Draft Law on the Indonesian National Army (RUU TNI) through the Critical Discourse Analysis (AWK) approach developed by Teun A. van Dijk. The main focus of the study is how the media can frame political issues that will be pros and cons in the public sphere as well as the representation of the power relations between the government and the military. This study uses a qualitative method with a reading-listening technique in news articles from online media that discuss the RUU TNI. Through Van Dijk's three-dimensional model (social cognition, social context, and text consisting of macro, micro, and superstructure structures), it was found that media discourse tends to show bias regarding the military's efforts to expand its role in the civilian sphere. The results of this study indicate that the media not only functions as a means of conveying information, but also as an ideological form that can produce or challenge existing power structures. Thus, the representation of the RUU TNI in the media can be a focus of the meaning of power that is important to criticize in the context of democracy and civilian supremacy over the military.